Calculation of the oxygen rate in the Ca1-xSrxFeO2.5+y compounds - TEDJANI, Salma (My University, 2016)
This work presents a study about calculation of the oxygen rate in the Ca1-xSrxFeO2.5+y brownmillerite compounds (x=0.5; 0.7; 0.9) based on the determination of its lattice parameters by x-ray powder diffraction from sample synthesized by solid solution method. Diffractogrammes were processed using the FULLPROF software depends on the "le bail" refinement, where we have arrived to achieving a mathematical model to estimate the oxygen rate through calculating its atomic packing factor(APF) which is the ratio of the atoms volume of the cell on the total volume.Ce travail présente une étude sur le calcul du taux d’oxygène dans les composés brownmillerite Ca1-xSrxFeO2.5+y (x=0.5; 0.7; 0.9) basés sur la détermination de ses paramètres de maille par la diffraction des rayons X sur poudre synthétisés par la méthode de solution solide. Les diffractogrammes ont été traitées à l'aide du logiciel de FULLPROF basés sur la méthode d'affinement "le bail", où on a arrivés à la réalisation d'un modèle mathématique permet d'estimer le taux d'oxygène à travers le calcul de ces compacités qui est le rapport de la somme des volumes des atomes de la maille au volume total de la maille étudiée.
memoire master physique
Keywords: Atomic packing factor(APF), Brownmillerite, Ca1-xSrxFeO2.5+y, FULLPROF software, oxygen rate; Compacité, Brownmillerite, Ca1-xSrxFeO2.5+y, FULLPROF, taux d'oxygène